How can special teachers aid successful kindergarten inclusion? Good practices in a district of Budapest - Báder, Melinda; Lukács, Szandra; Perlusz, Andrea (Gyermeknevelés Tudományos Folyóirat, 2022)
In our study, we would like to present an institutional development that furthered collaboration between mainstream kindergarten teachers and special education teachers, as well as the creation and functioning of a broader transdisciplinary team. This good practice can support the integration of children with special educational needs into kindergarten and the well-being of those involved. This process has grown in relevancy as integrated education becomes more widespread in Hungary, affecting more than 70% of SEN children today. According to the data published by the CSO (2020) for the 2019/2020 school year, 82% of children with special educational needs in the pre-school age group and 72% of those affected in the primary school age group receive integrated education.